Sago palm, Metroxylon sagu Rottb. - Flach, M.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
The true sago palm, Metroxylon sagu, has been described as mankind's oldest food plant with the starch contained in the trunk used as a staple food in southeast Asia. This booklet provides an overview of existing knowledge of the genus, with emphasis on genetic resources. Chapters cover the following topics: taxonomy, botanical description, centres of diversity, properties and uses, genetic diversity and folk taxonomy, breeding, production areas, ecology, agronomy and technology, limitations, prospects, and research needs. Two appendices are supplied listing: (1) existing collections; and (2) research workers. (Abstract © CAB ABSTRACTS, CAB International)